Differentiation of Live Streaming Strategies: Reception Analysis on the YouTube Channel DEANKT - Tatok, Muhammad Yudistira Putra Pamungkas; Sari, Eka Anisa (Syntax Literate, 2025)
This study explores various strategies employed by YouTube streamer DEANKT to shape audience reception and engagement through live streaming. Using a qualitative approach and reception analysis methodology, this research examines how these differentiated tactics—such as content segmentation, real-time audience interaction via live chats and donations (Saweria), and the implementation of membership tiers—distinctly compare to other channels and influence the dynamic relationship between the streamer and viewers. Observational data were collected from DEANKT's live streaming sessions, complemented by interviews with five active participants and an analysis of community interactions on platforms such as Discord. The findings highlight the effectiveness of DEANKT's diverse strategies in fostering audience loyalty, enhancing viewer participation, and creating a strong sense of community. Key results include the role of membership features in strengthening audience loyalty, the impact of donation-based interactions on viewer satisfaction, and the importance of diverse content segmentation in maintaining audience interest. Most respondents aligned with DEANKT's communication patterns, with the majority positioned in a dominant reception stance, indicating high levels of agreement and engagement with the streamer's strategies. This study contributes to the understanding of how personalized and interactive approaches can transform live streaming into an immersive and participatory experience, ultimately shaping the evolving landscape of digital media consumption.